(untitled) (Texas Journal of Medical Science, 2023)
The coronavirus has caused a wave of atypical acute respiratory illness in infected people. This virus has a high transmissibility between humans which has resulted in a worldwide pandemic. It has caused many deaths. No one has found an effective treatment for this problem. Epidemiological studies showed a variation in the severity of the infection among those infected with the virus and looking at the possible explanation for the variation in the severity of the infections. It also showed the involvement of calcium ions in the infection and the effect of the virus on the NLRP3 protein.